2020
DOI: 10.1016/j.sjbs.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-biochemical changes induced by zinc oxide nanoparticles

Abstract: Nanoparticles are now widely used in various aspects of life, especially zinc oxide nanoparticles (ZnNPs) that used in mouth washing, cosmetics, sunscreens, toothpaste and root canal flings. This research aims to determine the impact of ZnNPs on healthy mice's brain tissue. ZnNPs have caused major changes in the brain monoamines (dopamine, norepinephrine and serotonin) and ions such as Ca 2+ , Na + , K + and Zn 2+ . Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Moreover, our data for diabetic rats demonstrated that treatment with ZnONP efficiently restored GPx, SOD, and CAT activities by increasing the biosynthesis of GSH or reducing oxidative stress [62][63][64]. Conversely, as mentioned before, the intraperitoneal injection of 25 mg/kg ZnONP had no significant effect on the levels of CAT, SOD, and GSH in the brain, while treatment with ZnONP at a high dose decreased brain GSH and SOD and increased brain MDA levels [65].…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, our data for diabetic rats demonstrated that treatment with ZnONP efficiently restored GPx, SOD, and CAT activities by increasing the biosynthesis of GSH or reducing oxidative stress [62][63][64]. Conversely, as mentioned before, the intraperitoneal injection of 25 mg/kg ZnONP had no significant effect on the levels of CAT, SOD, and GSH in the brain, while treatment with ZnONP at a high dose decreased brain GSH and SOD and increased brain MDA levels [65].…”
Section: Discussionsupporting
confidence: 61%
“…Using this approach, Dkhil et al found that ZnO NPs induced perineural vascularization and vascular congestion ( Figure a,b). [ 176 ] TiO 2 NPs could also be translocated and accumulated in the brain, leading to oxidative stress, over‐proliferation of glial cells, tissue necrosis, and hippocampal cell apoptosis (Figure 7c–f). [ 177 ]…”
Section: Cytotoxicity Of Metal‐based Npsmentioning
confidence: 99%
“…Reproduced with permission. [ 176 ] Copyright 2020, Elsevier. c–f) Ultrastructure of hippocampal cell of mice caused by nasal administration of TiO 2 NPs for 90 consecutive days.…”
Section: Cytotoxicity Of Metal‐based Npsmentioning
confidence: 99%
See 2 more Smart Citations